A case of hemorrhagic pneumonitis resulting from heavy use of cannabis vaporizer products. Issue 1 (1st January 2019) - Bradley, Evan; Neavyn, Mark
Abstract: The use of vaporizer products for the consumption of nicotine and cannabis extracts has seen large increases in recent years, especially among young people, but the long-term health effects from the use of these products are unclear. Unsubstantiated claims suggest that vaporizers are safer than smoked tobacco or cannabis plant material, but recent reports of acute and severe respiratory illness resulting from their use has led to some jurisdictions temporarily banning their sale. These devices contain complex chemical preparations that include solvents, diluents, flavoring and possibly biproducts from heating elements within the device. Here, we report a case of 22-year-old otherwise healthy patient who developed hemorrhagic pneumonitis with hypoxic respiratory failure requiring intubation for respiratory support in a heavy user of cannabis vaporizer products. Extensive testing for inflammatory and infectious conditions did not reveal clear alternative explanation. Given the increasing availability and use of these products, emergency medicine practitioners and medical toxicologists should be aware of this potential toxicity and inquire about use of these products to patients presenting with respiratory symptoms and hemoptysis.